Task-based mirror therapy enhances ipsilesional motor functions in stroke: A pilot study. Issue 2 (April 2017) - Arya, Kamal Narayan; Pandian, Shanta; Kumar, Dharmendra
Summary: Objective: To examine the effect of Mirror therapy (MT) on dexterity, coordination, and muscle strength of the less-affected upper limb in stroke. Design: Pre-test post-test, single group, experimental design. Setting: Rehabilitation institute. Participants: Post-stroke hemiparetic chronic subjects (N = 21). Interventions: Forty sessions of MT using various tasks in addition to the conventional rehabilitation. Tasks such as lifting a glass, ball-squeezing, and picking-up objects were performed by the less-affected side in front of the mirror-box creating an illusion for the affected side. Main outcome measures: Minnesota Manual Dexterity Test (MMDT), Purdue Peg Board Test (PPBT), and Manual Muscle Testing (MMT) were used to measure the deficits of the less-affected side. Result: Post-intervention, the less-affected side of the participants exhibited significant improvement on MMDT (p < 0.001), PPBT (p < 0.001), and MMT (shoulder flexors, wrist extensors and deviators, and finger flexors-extensors; p = 0.005–0.046). Conclusion: In post-stroke hemiparesis, MT also led to the improvement in dexterity, coordination, and strength of the less-affected side. In addition to the affected side, the technique may augment the subtle motor deficits of the less-affected side.